Exploration of nutritional and bioactive peptide properties in goat meat from various primal cuts during in vitro gastrointestinal digestion and absorption - Pichitpon Luasiri; Papungkorn Sangsawad; Jaksuma Pongsetkul; Pramote Paengkoum; Chatsirin Nakharuthai; Saranya Suwanangul; Sasikan Katemala; Narathip Sujinda; Jukkrapong Pinyo; Jarunan Chainam; Chompoonuch Khongla; Supaluk Sorapukdee (My University, 2024)
This research aims to explore the nutritional and bioactive peptide properties of goat meat taken from various primal cuts, including the breast, shoulder, rib, loin, and leg, to produce these bioactive peptides during in vitro gastrointestinal (GI) digestion and absorption.
Keywords: Digestion; Loin; Chicken breast; Protein Hydrolysis and Bioactive Peptides